A mini review on biofilm-mediated water pollution: mechanistic interactions, preventive approaches, and removal strategies - Abd Rashid Syaida, Anati; Mat Jalil, Mohd Taufiq; Mahat, Mohd Muzamir; Rikson, Siburian; Raja Yahya, Mohd Fakharul Zaman (Faculty of Applied Sciences, 2025)
Biofilm formation significantly contributes to water pollution and infrastructure degradation in various industrial, urban, and marine environments. Biofilms can colonize various surfaces, including sediments, plants, and man-made structures. This colonization negatively impacts water quality and the integrity of water distribution systems. Biofilms can also harbor pathogenic microorganisms, posing health risks in drinking water systems. This mini-review discussed how biofilm-related processes, such as clogged pipes, bio corrosion, and marine biofouling, can lead to water pollution and their broader environmental and economic implications. Biofilm buildup can trap contaminants, weaken pipe structures, cause localized corrosion, increase the surface roughness of ship hulls, and contribute to higher operational costs and harmful emissions. Surface modification and managing hydrodynamic conditions effectively mitigate water pollution in various aquatic environments. Effective biofilm removal strategies include high-pressure water jets, ultrasonic treatment, enzyme-based cleaning, and oxidizing agents. In conclusion, biofilms are a major contributor to water pollution and infrastructure damage across various environments, highlighting the urgent need for innovative and effective biofilm management strategies. Combined with regulatory frameworks and public awareness, these measures can significantly reduce biofilm mediated water pollution's environmental and economic impacts.